A context-aware authentication method using blockchain for pervasive computing - Ng, Miao Xuan (2021)
802.11 networks are secured with authentication protocols like WEP or some variants of WPA. Currently, legit users must enter the correct Wi-Fi password for authentication in joining the Wi-Fi network. Although most Wi-Fi infrastructure these days can remember previously connected clients for faster re-authentication, it is time-consuming for users to manually key in long, complex passwords in joining any new Wi-Fi networks. Some existing Wi-Fi authentication is simplified by scanning QR codes or using password sharing for trusted devices. Replacing WPA keys with QR codes introduces additional security loopholes like QR code sharing to unauthorized users. Meanwhile, password sharing with trusted devices currently only works on Apple iOS devices and selected Android devices; while still requiring user interventions. In this project, a ‘pervasive Wi-Fi authentication method’ is proposed for automatic device authentication using Ethereum blockchain for faster, secure, and un-intrusive authentication. In this scheme, wireless access points (AP) are chained together using a shared ledger that contains a set of trusted devices Ethereum node ID(s). These trusted devices can easily hop to any previously unseen AP from a previous AP that shares the same ledger through blockchain verification. The proposed Ethereum-based authentication requires an average of 8.92ms compared to the standard WPA2 that requires 10.629ms for full Internet connectivity.